Degradasi Zat Warna Malachite Green Menggunakan Metode Sonolisis dengan Bantuan Katalis ZnO - Yollanda Bunga Osya; Hary Sanjaya (Jurnal Periodic Jurusan Kimia UNP, 2023)
Malachite green is a dye that is widely used in the textile industry. Malachite green has toxic properties that can cause cancer, skin and eye irritation, and respiratory toxicity. Malachite green is difficult to degrade in waste so it requires serious handling. This study aims to determine the optimum time and optimum mass of  ZnO catalyst for malachite green degradation by sonolysis method. The absorbance value was obtained using a UV-Vis spectrophotometer. The results of this study stated that the malachite green solution had a maximum wavelength of 617.2 nm. The optimum time to degrade malachite green with ZnO catalyst was obtained at 30 minutes with %D 85.04% and the optimum mass of catalyst to degrade malachite green with ZnO catalyst was obtained at 0.1 gram with %D 83.31%.